EFFECTIVENESS OF HEALTH EDUCATION ON PREGNANT WOMEN'S KNOWLEDGE ABOUT INFANT SLEEP QUALITY WITH BABY MASSAGE - Lina Humaeroh, Lina Humaeroh; Annisa Devi Permata, Annisa Devi Permata; Desy Syswianti, Desy Syswianti; Mellysa Wulandari Tasripin, Mellysa Wulandari Tasripin; Titi Purwitasari Handayani, Titi Purwitasari Handayani (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Garut City area is a sub-district in Garut Regency, West Java Province, Indonesia. The Garut City Government Center is in Tarogong Kidul District. Baby Massage is a light massage given to babies so that it provides a feeling of security, comfort and calm for the baby. Baby massage can be done by the mother, father or family members. The benefits of Baby Massage can result in positive changes in the baby. If done correctly, the baby can increase appetite and improve the quality of the baby's sleep. The involvement of STIKes Karsa Husada Garut as one of the stakeholders in the pregnant women's class is intended to enable them to actively participate in the program to increase pregnant women's knowledge about baby massage which can improve the quality of baby's sleep. For STIKes Karsa Husada, this activity is a community service activity which is one of the obligations of Higher Education Institutions in implementing the Tri Dharma. Activities will be held on Saturday 3 February 2024 at Pendopo Alun Alun Garut by providing education and practice regarding baby massage. Participants who attended were 30 pregnant women in the Garut City area